2010
DOI: 10.1039/c0nr00046a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and biocompatibility of “green” synthesized silver nanoparticles using tea polyphenols

Abstract: Since ancient times, people have taken advantage of the antimicrobial effects of colloidal silver particles. Aside from the medical prospects, silver nanoparticles are found in a wide range of commercially available consumer products ranging from cosmetics to household cleansers. Current synthetic methods for creating silver nanoparticles typically call for potentially hazardous chemicals, extreme heat, and produce environmentally dangerous byproducts. Therefore, it is essential that novel "green" synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
188
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(194 citation statements)
references
References 37 publications
6
188
0
Order By: Relevance
“…Our methodology shows that this mild and environmentally benign reductant can be used for the synthesis of surface supported metal nanoparticles, thus expanding its use beyond solution based nanoparticle synthesis [31,32]. Both Ag/C and Pd/C composite microspheres were tested in order to assess their activity as heterogeneous catalysts for organic synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our methodology shows that this mild and environmentally benign reductant can be used for the synthesis of surface supported metal nanoparticles, thus expanding its use beyond solution based nanoparticle synthesis [31,32]. Both Ag/C and Pd/C composite microspheres were tested in order to assess their activity as heterogeneous catalysts for organic synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently Varma and co-workers reported on the use of coffee or tea as a reducing agent for green synthesis of metal nanoparticles [31,32]. In this work we report on the use of coffee as a low-cost, green reagent for electroless deposition at room temperature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…9,10 More recently, therefore, silver nanoparticles (AgNPs) have been evaluated as a safer alternative to ionic silver. 1,[11][12][13][14][15][16][17][18][19][20] The recent work from our team showed that in comparison with silver, biomolecule-coated, photochemically-produced AgNPs can have both bactericidal and bacteriostatic properties with almost negligible cytotoxic effects. 12 We also showed that oxidation of Ag to AgO is most likely the cause of the cytotoxic effects observed with AgNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, plants are more suitable and compatible due to optimal environmental preservation, fast, simple production and high stability of particles (12,13). In addition, these organic nanoparticles can be used for molecular medicine as well as modern care in future.…”
Section: Introductionmentioning
confidence: 99%